Biodistribution of [(11)C]-Metformin and mRNA Expression of Placentae Metformin Transporters in the Pregnant Chinchilla - Overgaard, Maria Dahl (Contrast Media Mol Imaging, 2019)
BACKGROUND: While metformin is the first-line pharmacological treatment of diabetes mellitus type 2, this drug is not considered safe to use in pregnant women because of its unknown consequences for the fetus. In this study, we aimed to investigate the biodistribution of metformin in the pregnant chinchilla, a species exhibiting placental characteristics comparable with the pregnant woman. Furthermore, we aimed to investigate the expression of metformin transporters in humans and chinchillas, respectively, in order to evaluate the pregnant chinchilla as a novel animal model for the use of metformin in pregnancy. METHODS: Three chinchillas in the last part of gestation were injected with [(11)C]-metformin and scanned by PET/CT for 70 minutes to visualize the distribution. To investigate the difference in expression of placenta transporters between humans and chinchillas, PCR was performed on samples from five chinchilla placentae and seven human placentae. RESULTS: Dynamic PET with [(11)C]-metformin showed that the metformin distribution in chinchillas was similar to that in nonpregnant humans, with signal from kidneys, liver, bladder, and submandibular glands. Conversely, no radioactive signal was observed from the fetuses, and no metformin was accumulated in the chinchilla fetus when measuring the SUV. PCR of placental mRNA showed that the human placentae expressed OCT3, whereas the chinchilla placentae expressed OCT1. CONCLUSION: Since metformin did not pass the placenta barrier in the pregnant chinchilla, as it is known to do in humans, we do not suggest the chinchilla as a future animal model of metformin in pregnancies.